Numerical Investigation on the Applicability of Variable Compression Ratio in a Marine Two-Stroke Dual-Fuel Engine for Fuel Economy Improvement - Haosheng Shen; Daoyi Lu (Energies)
Marine two-stroke dual-fuel (DF) engines with a low-pressure gas concept normally face the problem of inferior fuel economy in diesel mode, mainly due to their lower compression ratio. To address this issue, a numerical study is performed to investigate the applicability of variable compression ratio (VCR) in a marine two-stroke DF engine, aiming at improving fuel economy in diesel mode. First, an engine simulation model is established and validated. Then, parametric investigation is performed to obtain insights on the effects of VCR on engine combustion, performance, and emissions. Finally, regression models of selected engine response variables are determined based on the response surface methodology (RSM), which are then optimized by particle swarm optimization (PSO) to obtain the optimal solution of engine setting parameters. The results show that with the application of VCR, the brake specific fuel consumption (BSFC) decreases by 9.65, 11.38, 11.13, and 11.27% at 25, 50, 75, and 100% maximum continuous rating (MCR), respectively. Meanwhile, the nitrogen oxides (NOx) emissions are maintained at the original levels, and the engine’s operating parameters are within specified limits. This study contributes to the delineation of the benefits and limits of VCR and provides a feasible method to facilitate the implementation of VCR in marine engines.